Douglas Southall Freeman papers - Freeman, Douglas Southall, 1886-1953.; Freeman, Douglas Southall, 1886-1953.; Freeman, Douglas Southall, 1886-1953.; Freeman, Douglas Southall, 1886-1953.; Freeman, Douglas Southall, 1886-1953.
Correspondence, diaries, speeches, writings, articles, notebooks, research materials, bibliographical material, clippings, printed matter, memorabilia, maps, photographs, and other papers pertaining primarily to Freeman's biographical and historical research and writing. Also documents his work as editor of the Richmond News Leader. Subjects include the American Revolution, Civil War, and national political and social affairs as well as affairs in Virginia, especially in Richmond, Va. Includes drafts and proofs of Freeman's works, R. E. Lee: A Biography (1934-1935), The South to Posterity: An Introduction to the Writings of Confederate History (1939), Lee's Lieutenants: A Study in Command (1946), and George Washington: A Biography (1948-1957). Correspondents include Frederic William Boatwright, Harry Flood Byrd, Colgate W. Darden, Dwight D. Eisenhower, Ellen Anderson Gholson Glasgow, Dumas Malone, George C. Marshall, Allan Nevins, A. Willis Robertson, and Harry S. Truman.
Biographer, editor, educator, and lecturer.
Collection material in English.
Finding aid available in the Library of Congress Manuscript Reading Room and at
Keywords: Boatwright, Frederic William, -- 1868-1951 -- Correspondence; Byrd, Harry F. -- 1887-1966 -- Correspondence; Darden, Colgate W. -- 1897-1981 -- Correspondence; Eisenhower, Dwight D. -- 1890-1969 -- Correspondence; Glasgow, Ellen Anderson Gholson, -- 1873-1945 -- Correspondence; Lee, Robert E. -- 1807-1870.; Malone, Dumas, -- 1892-1986 -- Correspondence; Marshall, George C. -- 1880-1959 -- Correspondence; Nevins, Allan, -- 1890-1971 -- Correspondence; Robertson, A. Willis -- 1887-1971 -- Correspondence; Truman, Harry S., -- 1884-1972 -- Correspondence; Washington, George, -- 1732-1799.; Richmond news leader; American newspapers -- Virginia -- Richmond; Confederate States of America -- History; Richmond (Va.) -- Politics and government; Richmond (Va.) -- Social conditions; Richmond (Va.) -- Social life and customs; United States -- History -- Revolution, 1775-1783.; United States -- History -- Civil War, 1861-1865.; United States -- Politics and government -- 20th century; United States -- Social conditions -- 20th century; United States -- Social life and customs -- 20th century; Virginia -- Politics and government -- 20th century; Virginia -- Social conditions; Virginia -- Social life and customs; Authors; Biographers; Editors; Educators; Lecturers